INFLUENCE OF SHADING ON I-V CHARACTERISTICS OF THIN FILM PV MODULES - Žnidarec , Matej; Topić, Danijel; Bušić, Josip (Journal of Energy Technology, 2024)
Photovoltaic (PV) systems are, numerically, the most widespread type of power plant that harvests renewable energy sources for electricity production. This paper investigates the influence of shading on the electrical characteristics of thin-film PV modules. Two types of thin-film PV modules are used: amorphous silicon and copper-indium-selenide. The electrical parameters of PV modules under various cases of shading are measured, analysed, and presented in tables and charts. A comparison between the electrical characteristics of crystalline silicon and thin-film PV modules under shading showed that thin-film PV modules have more consistent electrical parameters. I-V and P-V characteristics of shape of thin-film PV module are unaffected by shading. The power losses and efficiency of shaded modules are decreasing in linear relation to the increasing shaded area of a PV module.